Changes in the flight paths of pigeons based on extended spatial landmarks: Poster - Zaleshina, Margarita; Zaleshin, Alexander (University of Latvia, 2021)
The navigational behavior of birds is based on the spatial perception of the terrain over which they fly. Not only single reference points, but also continuous linear and areal objects can be visually perceived in flight and affect the flight path. In this work, we studied the features of the trajectories of pigeons during flights in order to identify the effect of discrete or continuous extended landmarks on spatial orientation. For this purpose we compared the GPS tracks of pigeons flying over weakly familiar terrain, and the visual features of this terrain, calculated on the basis of remote sensing data. Various cases of linear landmarks (alleys, rivers, roads) and boundaries between different surfaces (vegetation covers, water surfaces, rural or urban areas) were considered. Values of changes in flight parameters of pigeons were calculated for 150 flights over various mixed landscapes: natural forests, agricultural fields, urban and suburban areas, and the sea coast. Linear and area landmarks were recognized by satellite images of the territories, using spatial analysis methods to highlight the boundaries of particular homogeneous and heterogeneous patterns. As a result, typical reactions to extended objects during movement were revealed: either a long flight along the border with small fluctuations in the trajectory, or a sharp perpendicular crossing of the object’s border. In this study, all spatial data were processed using the geographical information system QGIS.
Keywords: spatial cognition; navigation; pigeon flight; QGIS